2014
DOI: 10.1002/ijc.29101
|View full text |Cite
|
Sign up to set email alerts
|

Risk of multiple myeloma is associated with polymorphisms within telomerase genes and telomere length

Abstract: Compelling biological and epidemiological evidences point to a key role of genetic variants of the TERT and TERC genes in cancer development. We analyzed the genetic variability of these two gene regions using samples of 2,267 multiple myeloma (MM) cases and 2,796 healthy controls. We found that a TERT variant, rs2242652, is associated with reduced MM susceptibility (OR = 0.81; 95% CI: 0.72–0.92; p = 0.001). In addition we measured the leukocyte telomere length (LTL) in a subgroup of 140 cases who were chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 48 publications
5
36
3
Order By: Relevance
“…Our finding disagrees with Campa et al that reported the association of the minor allele of rs2242652 with decreased risk of MM. Zhang et al found that TERT rs2242652 served as protective factors for the formation of hepatocellular carcinoma, which may be due to the reduced expression of TERT protein by this SNP.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our finding disagrees with Campa et al that reported the association of the minor allele of rs2242652 with decreased risk of MM. Zhang et al found that TERT rs2242652 served as protective factors for the formation of hepatocellular carcinoma, which may be due to the reduced expression of TERT protein by this SNP.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, there was no significant association of rs2242652 with relative telomere length. This observation was in agreement with Campa et al However, Bojesen et al result that this polymorphism was strongly associated with telomere length.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2 Several risk loci have been proposed and a few have been identified through candidate gene and genome-wide association studies (GWAS). [3][4][5][6][7][8][9][10] Some of these loci are involved in complex pathways related to cell cycle, cell proliferation and DNA repair, in which micro-RNAs (miRNAs) have a proven regulatory role. 11 MiRNAs are small non-coding RNA molecules, 20-25 nucleotides long, highly conserved throughout evolution.…”
Section: Cancer Epidemiologymentioning
confidence: 99%
“…Converging evidence of MM in monozygotic twins and familial aggregation of MM strongly suggest that MM aetiology has a robust genetic component as well . Several risk loci have been proposed and a few have been identified through candidate gene and genome‐wide association studies (GWAS) . Some of these loci are involved in complex pathways related to cell cycle, cell proliferation and DNA repair, in which micro‐RNAs (miRNAs) have a proven regulatory role …”
mentioning
confidence: 99%